Beginning spring framework 2 - Van de Velde, Thomas (Indianapolis, IN ; New Delhi : Wiley India Pvt. Ltd., 2008)
A guide to the Spring Framework provides instructions for designing and building Java server applications.
"Wrox programmer to programmer"--Cover.
Includes bibliographical references and index.
Keywords: Java (Computer program language); Application software -- Development; Web sites -- Authoring programs; Web site development